Firm-Level Labor Shortage Exposure - Harford, Jarrad; He, Qiyang; Qiu, Buhui (Review of Financial Studies, 2026)
We extract information from earnings call transcripts to develop a comprehensive and reliable measure of labor shortage exposure. After validating the measure at the state, industry, and firm levels, we show that firms with labor shortage exposures experience lower earnings call CARs, future stock returns and operating performance. Firms respond to labor shortages by substituting labor with capital and R&D investments, and by producing more production-process patents. Such responses help mitigate the negative effects on future performance. Our measure has broad applicability, and our findings provide new insight into labor-capital substitution in imperfectly competitive labor markets.